2013
DOI: 10.1163/15685381-00002906
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of artificial syntopy between Hydromantes italicus and H. ambrosii ambrosii (Amphibia, Plethodontidae)

Abstract: Thirty years ago, in 1983, an experiment of artificial syntopy put together two allopatric taxa of mainland European plethodontids: Hydromantes ambrosii ambrosii and H. italicus. An equal number of specimens of both species were released in a cave with a suitable environment but located outside the range of the genus. The aim was to test the effectiveness of the reproductive isolating mechanisms of these two moderately divergent taxa and, in the case hybridization would have occurred, to analyse the extent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The pattern observed at nuclear allozyme markers evidenced S. a. bianchii alleles strongly entering S. italicus gene pool and moving tens of kilometres away from the contact zone, while mtDNA showed a clean-cut subdivision with nearby populations having alternatively S. a. bianchii or S. italicus haplotyes (Nascetti et al, 1996;Ruggi et al, 2005). A similar pattern was evidenced also by an experiment of artificial syntopy between S. italicus and S. a. ambrosii in a cave located outside Speleomantes range and carried on for 30 years (Cimmaruta et al, 2013;Forti et al, 2005). The results…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The pattern observed at nuclear allozyme markers evidenced S. a. bianchii alleles strongly entering S. italicus gene pool and moving tens of kilometres away from the contact zone, while mtDNA showed a clean-cut subdivision with nearby populations having alternatively S. a. bianchii or S. italicus haplotyes (Nascetti et al, 1996;Ruggi et al, 2005). A similar pattern was evidenced also by an experiment of artificial syntopy between S. italicus and S. a. ambrosii in a cave located outside Speleomantes range and carried on for 30 years (Cimmaruta et al, 2013;Forti et al, 2005). The results…”
Section: Discussionsupporting
confidence: 82%
“…The pattern observed at nuclear allozyme markers evidenced S. a. bianchii alleles strongly entering S. italicus gene pool and moving tens of kilometres away from the contact zone, while mtDNA showed a clean‐cut subdivision with nearby populations having alternatively S. a. bianchii or S. italicus haplotyes (Nascetti et al, 1996; Ruggi et al, 2005). A similar pattern was evidenced also by an experiment of artificial syntopy between S. italicus and S. a. ambrosii in a cave located outside Speleomantes range and carried on for 30 years (Cimmaruta et al, 2013; Forti et al, 2005). The results showed that the two taxa were able to produce viable hybrids and recombinants, but also that the crosses have been asymmetric, with pure S. a. ambrosii constituting the bulk of the population and the recombinant genotypes largely characterized by S. ambrosii nuclear alleles associated with S. italicus mitochondrial haplotypes (Cimmaruta et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…Studies on hybrid populations of Speleomantes have been extremely limited [8,11], leaving their morphological and ecological traits largely unknown. Despite our limited sample size, especially in regards to diet, we were able to obtain interesting information to provide the basis for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty years after its introduction, the population was genetically characterized and none of the individuals had a pure genotype. For 77% of individuals, the majority of alleles (>75%) matched alleles specific to S. a. ambrosii; for 6% of individuals, the majority of alleles matched those of S. italicus; and for 16% of individuals, alleles of S. a. ambrosii and of S. italicus were recombined [11]. However, the lack of ecological information on this population prevents us from evaluating the potential difference between these non-natural hybrids and the hybrids living in the natural hybrid zone, and to assess the trophic relationships between these populations and the local fauna [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data show a broad correspondence between the presence of “misplaced” haplotypes into a nuclear gene pool with introgression events and interpreting the cito-nuclear discordance as support for the mito-genome introgression hypothesis [ 71 – 73 ]. Accordingly, experimental data showed that in Hydromantes species introgression may lead to the capture of “foreign” haplotypes into the gene pool of one species although maintaining differentiated nuclear genomes [ 74 ]. In this view, the nesting of the “Finalese” group into the mitochondrial subclade A opposed to its external position according to nuclear data can be explained by a contact between the two sub-clades followed by mtDNA introgression into the “Finalese” populations.…”
Section: Discussionmentioning
confidence: 99%